Monstrous contemplation: Frankenstein, Agamben, and the politics of life. Issue 4 (21st April 2018) - del Valle Alcalá, Roberto
ABSTRACT: In his recent book L'uso dei corpi, Giorgio Agamben investigates the philosophical genealogy of his central concept of inoperosità through a reconsideration of the classical notion of chresis or 'use'. According to Agamben, the latter points to an alternative constitution of human nature, one that would not be guided by a principle of necessary actualisation (energeia), would not exhaust itself in the realisation of an end (ergon), but would rather preserve its potentiality in a thoroughly non-subjective ('contemplative') relation of the body to itself. For Agamben, it is only through the recognition and mobilisation of this alternative foundation of the human, that the pervasive division of life (between natural and political, 'bare' and 'autarchic', zoe and bios) upon which modern politics is premised, can be overcome. In this article, I propose to read in Mary Shelley's Frankenstein an instructive rehearsal of these fundamental concepts, focusing on the possible meanings that the notion of monstrosity may acquire when placed against the backdrop of modernity's commitment to energeia and its associated biopolitical mechanisms.